APAKAH PENGUNGKAPAN ESG DAN PELAPORAN KEBERLANJUTAN MENINGKATKAN KINERJA KEUANGAN? PERAN MODERASI UKURAN PERUSAHAAN - Nurul Hidayah; Tantina Haryati (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2026)
This research examines the impact of Environmental, Social, and Governance (ESG) disclosure and sustainability reporting on financial performance, and assesses if these links are moderated by company size. This research contributes to the sustainability literature by examining how company size moderates the relationship between ESG, sustainability reporting, and financial performance. The research sample includes energy sector listed on the IDX from 2022 to 2024, totaling 91 companies. The sample was selected using purposive sampling. From the sample selection process, 22 companies met the criteria, yielding 66 observations. Panel data regression was used for analysis. Results show that ESG disclosure by individual pillars does not significantly affect financial performance, while sustainability reporting has a significant negative impact. Company size does not moderate the link between ESG disclosure or sustainability reporting and financial performance, suggesting that financial outcomes from ESG practices are consistent across company sizes. These findings suggest that both large and small companies are equally motivated to disclose sustainability information.